Planejamento do Carregamento de Veículos Elétricos Atendidos por um Eletroposto isolado - Ferreira, Raisa Tatiana (2018)
The main goal of this work is to achieve the management of the recharge of electrical vehicles by a stand-alone microgrid, poweredby renewable energy (solar and wind). As a first step, anenergy management model was written and solved with the help of the software AMPL. The microgrid in question is an EV-charging station, with many uncertainties regarding its operationdue to the random nature of its power sources and loads.For this reason,the Monte Carlo methodwas used to forecasta probability density curve regarding the arrival of vehicles. Usinghistorical data, the probability density functionrelated to sun radiation and wind speed wascalculated and, using these functions,random solar radiation and wind speed data wasgenerated.Finally, the data obtained wasapplied to the energy management model presented in this dissertation, aiming to maximize the amount of energy supplied to the electrical vehicles, clients of the EV-charging station.